The left inferior frontal gyrus is causally linked to vocal feedback control: evidence from high-definition transcranial alternating current stimulation. (14th November 2022) - Li, Tingni; Chang, Yichen; Zhao, Shuzhi; Jones, Jeffery A; Chen, Xi; Gan, Chu; Wu, Xiuqin; Dai, Guangyan; Li, Jingting; Shen, Ying; Liu, Peng; Liu, Hanjun
Abstract: Current models of speech motor control propose a role for the left inferior frontal gyrus (IFG) in feedforward control of speech production. There is evidence, however, that has implicated the functional relevance of the left IFG for the neuromotor processing of vocal feedback errors. The present event-related potential (ERP) study examined whether the left IFG is causally linked to auditory feedback control of vocal production with high-definition transcranial alternating current stimulation (HD-tACS). After receiving active or sham HD-tACS over the left IFG at 6 or 70 Hz, 20 healthy adults vocalized the vowel sounds while hearing their voice unexpectedly pitch-shifted by ±200 cents. The results showed that 6 or 70 Hz HD-tACS over the left IFG led to larger magnitudes and longer latencies of vocal compensations for pitch perturbations paralleled by larger ERP P2 responses than sham HD-tACS. Moreover, there was a lack of frequency specificity that showed no significant differences between 6 and 70 Hz HD-tACS. These findings provide first causal evidence linking the left IFG to vocal pitch regulation, suggesting that the left IFG is an important part of the feedback control network that mediates vocal compensations for auditory feedback errors.